1997
DOI: 10.1161/01.atv.17.6.1163
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Compliance in Obese Subjects Is Improved With Dietary Plant n-3 Fatty Acid From Flaxseed Oil Despite Increased LDL Oxidizability

Abstract: The compliance or elasticity of the arterial system, an important index of circulatory function, diminishes with increasing cardiovascular risk. Conversely, systemic arterial compliance improves through eating of fish and fish oil. We therefore tested the value of high intake of alpha-linolenic acid, the plant precursor of fish fatty acids. Fifteen obese people with markers for insulin resistance ate in turn four diets of 4 weeks each; saturated/high fat (SHF), alpha-linolenic acid/low fat (ALF), oleic/low fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 40 publications
5
97
1
6
Order By: Relevance
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical trials have showed that n-3 fatty acids (fish oil, flaxseed oil or purified eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) supplementation can improve arterial elasticity in normotensive subjects with dyslipidemia, obesity or diabetes (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In the Health Professional Follow-up Study the relative risk of CHD for a one energy-% increase in alpha-linolenic acid was 0.41 after adjustment for standard risk factors and intake of ®bre and total fat (Ascherio et al, 1996). An increase in arterial compliance by dietary alpha-linolenic acid, which might decrease the work load of the heart, might contribute to a reduced risk in CHD by alphalinolenic acid (Nestel et al, 1997). Arterial compliance is also increased by marine n-3 PUFA in diabetics.…”
Section: Does Consumption Of ®Sh Protect Against Cancer?mentioning
confidence: 99%
“…In epidemiological studies no relation could be detected between ®sh intake and blood pressure. The limited data on alpha-linolenic acid show variable effects (Salonen, 1991;Nestel et al, 1997).…”
Section: What Is the Outcome On Diabetes?mentioning
confidence: 99%
“…In addition, dietary fish oil supplementation for 6 weeks improved arterial compliance in patients with non-insulin dependent diabetes (McVeigh et al, 1994). Furthermore, n-3 rich flaxseed oil supplementation for 4 weeks increased systemic arterial compliance in obese subjects (Nestel et al, 1997). Thus, the association between stanol ester margarine use and higher arterial compliance may partly be mediated by a linolenic fatty acid.…”
Section: Discussionmentioning
confidence: 99%